Pot Skirt Configuration on the UB-03 Biomass Stove: Taguchi Approach Optimization - Bayu Rudianto; Maghriza Iskhak; Dedy Eko Rahmanto; Miftah Hijriawan (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2024)
A biomass stove is a technology that can utilize biomass fuel as an alternative energy source. This stove is considered effective for saving fossil energy because it uses fuels such as wood, waste, and plants so that it can reduce the effects of global warming because it can minimize the emissions it produces. In its technological development, UB-03 is a biomass stove product with compact construction and affordable prices for rural communities. However, there needs to be an increase to produce more efficient performance. In this case, additional configurations in the form of a pot skirt can be used to increase the efficiency of the biomass stove. The pot skirt is a device that focuses the fire’s direction on the load to minimize wasted heat and increase the efficiency of the biomass stove. This study used the Water Boiling Test (WBT) method for experimental testing. In addition, the Taguchi method was used to analyze the data obtained. This study aims to determine the optimum conditions of the biomass stove with the addition of a pot skirt using the Taguchi method with orthogonal array L9 (33) with three factors, namely angle (64°, 65°, 66°), number of holes (9,10,11) and hole diameter (0.8 cm, 1 cm, 1.2 cm). The results of this study indicate that the optimal configuration obtained is by adding a pot skirt at an angle of 65° with 9 holes and a hole diameter of 1 cm, where the highest efficiency value is obtained, namely 21.19%.